Attitude and entrepreneurial culture in the university entrepreneurs of the municipality Victoria de Durango - Hernández-Chavarria, Juana; Lechuga-Névarez, Mayela del Rayo (REGEPE Entrepreneurship and Small Business Journal, 2023)
Objective of the study: Analyze the entrepreneurial attitude and culture in university entrepreneurs in the Victoria de Durango municipality, Mexico. Methodology/approach: The unit of analysis was 152 university entrepreneurs, they were studied using a mixed approach: quantitative through a questionnaire and through a statistical analysis with a structural and qualitative equation model through interviews. Main results: The main findings show that the entrepreneurial attitude and the entrepreneurial culture are significantly related, influencing the development of university entrepreneurship; where the most significant factors are "Opportunity" and "Innovation", which shows that they are entrepreneurs with initiative to identify opportunities in the market, but not only that, but the innovation component is added, which shows that they are professionals who seek to break with a traditional scheme and have a more proactive vision to offer products with greater added value that could ensure their permanence in the market. Theoretical/methodological contributions: This work is relevant because it allows us to know the motivations that graduates of public Higher Education Institutions (HEIs) have to create entrepreneurships and what are the main elements that influence the decision to undertake. Relevance/originality: The results offer information on the motivations, needs and obstacles faced by entrepreneurs and that could be used to outline selective public policies to encourage the growth of university entrepreneurship as a strategy to promote qualified employment. Social/management contributions: Studying the entrepreneurial attitude and culture of university entrepreneurs allows the creation of companies with high technological and technological content. innovation in products and processes.